Relationship between organizational justice, organizational commitment, job satisfaction, employee engagement and organizational citizenship behavior among local government employees in Lagos State, Nigeria - Amaka, Ikenna Jennifer (2020)
Organizational Citizenship Behavior (OCB) is known to be one of the most important concepts in organizational effectiveness and efficiency on quality and productivity. Determining how OCB contributes indirectly to an organization through the organization’s social system has been of increasing interest to both scholars and managers. Although the antecedents of organizational citizenship behaviors have been largely investigated by researchers, there is still little research considering the results of organizational citizenship behavior on public organization. While it is evident that there are numerous crucial determinants of OCB that are known to enhance organizational effectiveness, efficiency, productivity and overall performance, research with respect to the specific factors that promote OCB under different organizational contexts is scarce. Thus, this study tends to examine the determinants of organizational citizenship behavior among employees of local government areas in Lagos State, Nigeria. This study employed multi-stage sampling techniques on 400 employees of three selected local government areas in Lagos. A self-administered questionnaire was distributed between the months of February and March, 2018 and the data collected was analyzed using SPSS version 22.0. The result of the descriptive analyses obtained indicated that there is high level of employee job satisfaction, organizational commitment, organizational justice, employee engagement as well as high level of OCBs. Also result of a Pearson correlation revealed that the employee job satisfaction, organizational commitment, employee engagement and organizational justice all have significant (p<0.001) and positive relationship with organizational citizenship behavior (OCB). Result of the multiple regression indicated that Job satisfaction has the most significant influence on organizational citizenship behavior (p<0.001), followed by the organizational commitment, the employee engagement, and variable with least effect was the organizational justice. Based on the outcome of the study, it can be concluded all the independent variables have positive and significant influence on OCB and therefore recommended that the local government authorities should device a means that would enhance organizational citizenship behavior among local government employees.